ONE-STAGE RECONSTRUCTION OF INJURED SOFTTISSUE ANATOMIC STRUCTURES OF THE FOREARM LOWER THIRD - B. Sh. Minasov; M. M. Valeyev; E. M. Biktasheva; R. R. Yakupov; T. R. Mavlyutov (Вестник хирургии имени И.И. Грекова)
.